Low-cost instrument for tracing current-voltage characteristics of photovoltaic modules - Leite, Vicente (2012)
This paper presents a simple, robust and low-cost instrument for tracing current- and power-voltage characteristics of photovoltaic modules or low voltage strings using either an oscilloscope or a LabVIEW application developed for this purpose. It consists of a flexible electronic circuit, developed from a previous work, based on a fast varying load, built with a power MOSFET, which is controlled by means of a suitable gate-source voltage control signal in order to improve the tracing of current- and powervoltage characteristics on an oscilloscope. The new developments of this work include a low-cost DAQ system and an application developed in LabVIEW, which enhances the functionalities and flexibility of the current-voltage tracer. The robustness was strongly improved in view of field tests for fault diagnosis analysis. All details of the electronic circuit are shown in this paper and experimental results obtained with the new instrument are presented